Analisis Pasar Modal Di Indonesia Studi Pada Perusahaan Manufaktur - Amar, Anis Tassya Regitha Putri; Atmadja, Melvin; Veronica, Novita (SALAM: Jurnal Sosial dan Budaya Syar-i, 2023)
The Government of Indonesia (GoI) recently enacted Government Regulation Number 72/2016 concerning Shares Subscription and Arrangement of State Capitals in State-Owned Enterprises (BUMN) (hereinafter referred to as “PP Holding BUMN”). The Indonesian Ministry for BUMN (“Meneg BUMN”) proposes, that the Holding of BUMN will cover six core economic sectors: (1) Energy, (2) Mineral extraction, (3) Financial service, (4) Highway infrastructure/construction, (5) Property (real estate), (6) Food. BUMN is principally regulated in Article 33 paragraphs 1, 2, and 3 of the Indonesian Constitution 1945, which provides a legal basis for the state-owned monopolies by BUMN. On one hand, the GoI argues that Holding of BUMN is necessary because it would bring beneficial impacts, such as the strengthening of corporate performance by creating synergies and economies of scale and reducing inefficiencies in operations and financing; professionalizing the management system by distancing BUMN from unreasonable politics; and relieving the Government of its direct responsibilities of overseeing all the BUMN dispersed across various industries. On the other hand, there are public pervasive concerns that PP Holding BUMN would lead to unlawful privatization of BUMN, and this led to the public filing an appeal for a Judicial Review from the Indonesian Constitutional Court. Accordingly, this research attempts to analyze the Holding of BUMN under PP Holding BUMN, the Constitutional Law Analysis of Judicial Review over the Government Regulation Number 47/2017, as well as Law Number 19 year 2003 on BUMN.Keywords: Holding of Indonesian State-Owned Company (BUMN); Government Regulation Number 72/2016; Judicial Review; Indonesian Constitutional Court (MKRI) AbstrakPemerintah Indonesia baru-baru ini menetapkan Peraturan Pemerintah Nomor 72 Tahun 2016 tentang Langganan Saham dan Penyelenggaraan Modal Negara pada Badan Usaha Milik Negara (BUMN) (selanjutnya disebut